Analisis Keterampilan Dasar Mengajar Guru Dalam Proses Pembelajaran IPS Di Sekolah Dasar - Annisa Qomariah; Afdal; Andi Alif Tunru (Shofanah Media Berkah, 2025)
This study aims to analyze the of teachers' basic teaching skills and identify the constraints faced in the Social Studies (IPS) learning process in Grade V at SDN 011 Samarinda Utara. The research is motivated by the importance of pedagogical competence in revitalizing Social Studies material, which tends to be theoretical and information-dense for elementary school students. The research method used is descriptive qualitative. Data were collected through direct observation, in-depth interviews with classroom teachers, and documentation studies. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The results indicate that the Grade V teacher has implemented set induction, explaining, and classroom management skills effectively through a contextual approach based on the local environment of Samarinda. However, higher-order questioning skills and small-group discussion leadership remain suboptimal. The primary obstacles identified include limited time allocation, high student density per class (overcrowded classrooms), and technical constraints regarding digital media infrastructure. This study concludes that teachers must perform creative adaptations in applying teaching skills to overcome infrastructure limitations to create a more interactive and meaningful Social Studies learning experience.